2015
DOI: 10.1093/jee/tou024
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Bacillus thuringiensis spp. galleriae Against Rice Water Weevil (Coleoptera: Curculionidae) for Integrated Pest Management in California Rice

Abstract: Rice water weevil (Lissorhoptrus oryzophilus Kushel) is the most damaging insect pest of rice in the United States. Larval feeding on the roots stunt growth and reduce yield. Current pest management against the weevil in California relies heavily on pyrethroids that can be damaging to aquatic food webs. Examination of an environmentally friendly alternative biopesticide based on Bacillus thuringiensis spp. galleriae chemistry against rice water weevil larvae showed moderate levels of activity in pilot studies.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…kurstaki or B. thuringiensis subsp. galleriae , have also been shown to have insecticidal activity against various coleopterous insects, including the family Curculionidae . This helps to explain the results found in this study, where the status of this strain has been confirmed.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…kurstaki or B. thuringiensis subsp. galleriae , have also been shown to have insecticidal activity against various coleopterous insects, including the family Curculionidae . This helps to explain the results found in this study, where the status of this strain has been confirmed.…”
Section: Discussionsupporting
confidence: 82%
“…B. thuringiensis subsp. galleriae was first reported in another weevil species, the rice water weevil, Lissorhoptrus oryzophilus . Compared with the effects of other B. thuringiensis strains against other coleopteran pests, the effects of the HA isolate on RPW in this study were relatively slow acting, although the larval survival rate did gradually decrease with increased concentrations and with the extension of exposure times (Fig.…”
Section: Discussionmentioning
confidence: 49%
“…These results are in contrast to those found for the toxicity of the same Bt galleriae formulation on the Rice water weevil ( Lissorhoptrus oryzophilus , Coleoptera: Curculionidae) and the Alfalfa weevil ( Hypera postica , Coleoptera: Curculionidae). Larval mortality ranged between 50–80% and 27–60%, respectively, for L. oryzophilus and H. postica 20,25 . For adults, a 50–90% reduction in defoliation and 50–80% mortality were recently reported for the Japanese beetle ( Popillia japonica , Coleoptera: Scarabaeidae) 26 and 100% mortality for the bean weevil Acanthoscelides obtectus (Coleoptera: Chrysomelidae) 37 .…”
Section: Discussionmentioning
confidence: 97%
“…In this pilot study, we tested concentrations suggested by product labels and previous literature examining the effect of these formulations (not transgenic plants) on Coleopteran late-instar larvae or adults (if available), and in Diptera for Bt. [22][23][24][25][26] Concentrations (percentage of product in treatment solution; mass or liquid to volume ratios, g:vol or vol:vol) ranged from 0.1% to 25% in these studies and instructions, depending on the strain. As in previous studies, we took into account the number of colony-forming units (CFU; no.…”
Section: Testing Toxicity Of Individual Bt Formulationsmentioning
confidence: 99%
“…galleriae (Btg) have proven to be an environmentally friendly alternative against rice water weevil larvae. Studies indicate that Btg granular formulation has biological activity against this target pest and performs as well as the pyrethroids insecticides [73], showing promising potential for rice water weevil control.…”
Section: Bacillus Thuringiensis Development On Rice Cropsmentioning
confidence: 99%